2003
DOI: 10.1093/humrep/deg228
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA fragmentation decreases the pregnancy rate in an assisted reproductive technique

Abstract: The proportion of sperm with DNA fragmentation appears to be potentially useful as a predictor of ICSI outcome, whereas embryo quality based on morphological criteria, appeared unaffected by DNA fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
268
3
28

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(328 citation statements)
references
References 23 publications
24
268
3
28
Order By: Relevance
“…Although the different thresholds have applied to assisted reproduction samples, and no IVF or ICSI pregnancies were reported when the DFI of the neat semen sample was >27 % [28]. Similar cut-offs of 28 % for 33 IUI/IVF/ICSI/ cycles [36], 20 % in a group of 104 IVF and ICSI cycles [4] and 27 % for 113 IVF and ICSI cycles have been reported [27]. [10] have also shown the importance of this chromatin assay as an independent predictor in assisted reproduction outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Although the different thresholds have applied to assisted reproduction samples, and no IVF or ICSI pregnancies were reported when the DFI of the neat semen sample was >27 % [28]. Similar cut-offs of 28 % for 33 IUI/IVF/ICSI/ cycles [36], 20 % in a group of 104 IVF and ICSI cycles [4] and 27 % for 113 IVF and ICSI cycles have been reported [27]. [10] have also shown the importance of this chromatin assay as an independent predictor in assisted reproduction outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Other reports, such as Martin and co-authors, demonstrated that oligozoospermic samples have an increased probability of sperm chromosome abnormality, whether from mild to severe oligozoospermia [23], whereas chromosomal abnormalities of spermatozoa are not higher in aging males. It has been shown that low sperm morphology is associated with DNA fragmentation in men with an average age of 35 [24]. In addition, the same investigators reported that an increased DNA fragmentation rate decreases the pregnancy rate.…”
Section: Discussionmentioning
confidence: 97%
“…Young women, of an average age of 24 (range [20][21][22][23][24][25][26], were accepted into the Egg Donation Program (EDP) cycles. All of these women were healthy, had normal menstrual cycles and no determined pathology.…”
Section: Oocytes Donation and Fertilizationmentioning
confidence: 99%
“…With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered. In particular, long periods of incubation, as well as shear stresses due to centrifugation, increase ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%